Long-Term Inhibition of Notch in A-375 Melanoma Cells Enhances Tumor Growth Through the Enhancement of AXIN1, CSNK2A3, and CEBPA2 as Intermediate Genes in Wnt and Notch Pathways - Keyghobadi, Faezeh; Mehdipour, Maryam; Nekoukar, Vahab; Firouzi, Javad; Kheimeh, Abolfazl; Nobakht Lahrood, Fatemeh; Azimian Zavareh, Vajihe; Azimi, Masoumeh; Mohammadi, Mahsa; Sodeifi, Niloofar; Ebrahimi, Marzieh (Frontiers in Oncology, 2020)
Notch suppressing by γ-secretase inhibitors is a valid approach against melanoma. However, most of studies have evaluated the short-term effect of DAPT on tumor cells or even cancer stem cells. In the present study, we surveyed the short-term and long-term effect of DAPT on the stem cell properties of A375 and NA8 as melanoma cell lines. The effects of DAPT were tested both in vitro and in vivo, using xenograft models. In A375 with B-raf mutation, DAPT decreased the level of NOTCH1, NOTH2, HES1, as downstream genes of the Notch pathway. This was accompanied by enhanced apoptosis post 24h treatment, arrest in the G2-M phase and impaired ability of colony and melanosphere formation at short-term. Moreover, tumor growth also reduced during 13 days of treatment. However, long-term treatment of DAPT promoted tumor growth in the xenograft model and enhanced the number and size of colonies and spheroids in vitro. The gene expression studies confirmed the upregulation of Wnt and Notch downstream genes as well as AXIN1, CSNK2A3, CEBPA2 following the removal of Notch inhibitor in vitro and in the xenograft model. Moreover, the Gomperta-based mathematical model determined a new drug resistance-term in the present study. Our data supported that the long-term and not short term inhibition of Notch by DAPT may enhance tumor growth and motility through up regulation of AXIN1, CSNK2A3, CEBPA2 genes in B-Raf mutated A375 cells.